Chapter 10: Glucose control: insulin therapy - The Society for Endocrinology Metabolism and Diabetes of South Africa (South African Family Practice)
Insulin and its analogues lower blood glucose by stimulating peripheral glucose uptake, especially by skeletal muscle and fat, and by inhibiting hepatic glucose production. Insulin inhibits lipolysis and proteolysis, and enhances protein synthesis.